Understanding Dilalah Amr and its Implementation in the Prayer Method among Muhammadiyah, Al Washliyah, and Nahdlatul Ulama - Hadi Munawwar; Asmuni Asmuni; Hasan Matsum (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
To understand how the scholars of the Mazhab understand Dilalah Amr, both from the Qur'an and Hadith sources, the method used in determining a command (Amr) for obligation or others in the prayer ritual, and its implementation towards the procedures of performing the prayer ritual among the Muhammadiyah, Al Washliyah, and Nahdlatul Ulama communities. This research is a normative study with a literature research method using references from relevant literature related to Amr sourced from the Qur'an and Hadith verses. The jurists (Fuqoha) in understanding Dilalah Amr use several methods, namely: (1) using Qarinah Qauliyah and Haliyah, (2) giving weight to stronger evidence to be used as Qarinah, (3) using the method of Qiyas, (4) using the actions of the people of Madinah as reference, (5) using Ijma, and (6) using the method of Naskh. In relation to the prayer procedure of Muhammadiyah, they do not recognize the terms of pillars (rukun), obligatory (wajib), and recommended (sunnah) in prayer. What is recognized is the method of performing obligatory prayer. Meanwhile, among Al-Washliyah, they still use the terminologies of the scholars of Usul Fiqh such as pillars, obligatory, and recommended in prayer. Similarly, Nahdlatul Ulama adheres to the four Mazhabs.